(untitled) (Papeles, 2018)
Neurosciences have generated great interest and enthusiasm in recent decades in various fields of knowledge. One of these fields is education. As a result the term neuro-education was suggested. However, there is a gap between the two areas: neuroscience has accumulated experimental evidence about the biological basis of emotions, cognitive processes and critical periods. Education has few works that show the extrapolation of this evidence in educational processes. The gap neuroscience-education is because neuroscientists have little relation to education and teachers do not have a solid background in neurosciences. This, added to the intuitive work of experts in educational processes, has induced the creation of neuromyths, which generates confusion and eludes the possibility of a true integration between neuroscience and education. To reduce this gap, it is necessary training for teachers in neuroscience topics, training for neuroscientists in education and, also, research and dissemination of results, which will validate or discard experimental evidence. The results of thosestudies will be a key to guide educational policies that will result in improving thequality of education for future generations.